2002
DOI: 10.1046/j.1365-2206.2002.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Training foster carers in challenging behaviour: a case study in disappointment?

Abstract: 2001), published as we completed our own study, which found no clear evidence of the impact of a carer training programme on foster children's emotional and behavioural functioning. Our enquiry lends support to their valuable findings; however, our research design differs in many respects and will reveal different insights into this complex field. We return to Minnis and Devine later but first we set out the parameters of our own investigation, which recognized that challenging behaviour is not a single entity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…2006; Chamberlain et al . 2008; Sprang 2008) and two UK (Minnis 2001; MacDonald & Turner 2005) RCTs and one UK prospective cohort study (Pithouse et al . 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2006; Chamberlain et al . 2008; Sprang 2008) and two UK (Minnis 2001; MacDonald & Turner 2005) RCTs and one UK prospective cohort study (Pithouse et al . 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the effect of training and support interventions for foster carers on child problem behaviours (potentially including physical aggression, anxiety/depression, criminal behaviour and screaming; Pithouse et al . 2002; MacDonald & Turner 2005; Dozier et al .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, these studies tended to be on the ‘more recent’ end of the continuum, with studies in the last five years often having the most sophisticated designs and most positive results. Pithouse, Hill-Tout, and Lowe’s (2002) study of training aimed at managing challenging behavior showed limited impact on parents’ capacity or children’s conduct. Chamberlain, Moreland, and Reid’s (1993) study of increased stipends and support, in contrast, showed positive effects on children’s behavior.…”
Section: Evidence Base For Foster Parent and Treatment Foster Parent mentioning
confidence: 99%
“…The management of challenging behaviour through specific strategies and parenting style has been the focus of training packages for foster carers. However, the efficacy of this training to ameliorate challenging behaviour and increase the capacity of foster carers to cope has been shown to have no significant effect in comparison to foster carers not in receipt of training (Macdonald & Turner, 2005;Pithouse, Hill-Tout, & Lowe, 2002).…”
Section: Introductionmentioning
confidence: 99%